Pembelajaran E-Learning Perkembangan Anak di Jurusan Psikologi - Khoirunnisa, Riza Noviana; Dewi, Damajanti Kusuma; Nurwidawati, Desi (Universitas Negeri Surabaya, 2018)
Conventional learning method is viewed to be less effective because it poses the problems of space and time. Information Technology offers a method for more effective online learning called e-learning. This research aims to develop e-learning for the module of Child Development at Department of Psychology Universitas Negeri Surabaya. This study was a developmental research project that used the method of ADDIE (Analysis, Design, Development, Implementation, Evaluation). This model was chosen because the stages of its development are deemed appropriate especially for the refinement and implementation of e-materials in online system which facilitates the interactions among students and between the students and lecturers. The subjects of this study were 34 undergraduate psychology students who participated in the module of Child Development. This study was conducted during four meetings. The results of this study were e-material products which were uploaded in online learning system. The e-materials have been validated by experts. A questionnaire to record students’ responses on the e-materials was used. The analysis on the data resulted from students’ responses shows that there is no significant effect of the e-learning application in the module of Child Development on the students’ learning achievement. Keywords: Online learning, child development module, ADDIEAbstrak: Metode pembelajaran konvensional dirasakan menjadi kurang efektif karena terbentur masalah ruang dan waktu. Teknologi Informasi menawarkan metode pembelajaran yang dinamakan metode e-learning. Penelitian ini bertujuan untuk mengembangkan pembelajaran e-learning pada mahasiswa yang memprogrram mata kuliah Perkembangan Anak di Jurusan Psikologi. Metode penelitian menggunakan Model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Model ini dipilih karena tahapan-tahapan pengembangannya dipandang sesuai terutama untuk penyempurnaan dan implementasi bahan ajar e-materi dalam sistem online dan fasilitas interaksi mahasiswa dengan dosen dan antar mahasiswa. Subjek penelitian ini adalah mahasiswa yang memprogram mata kuliah Perkembangan Anak sejumlah 34 mahasiswa. Pelaksanaan penelitian ini dilaksanakan selama empat kali pertemuan. Hasil penelitian ini adalah produk e-material yang telah divalidasi oleh ahli. Kuesioner disebarkan untuk diisi oleh mahasiswa dengan tujuan untuk mengukur respon mereka atas penggunaan e-learning dan e-material. Hasil analisis data menunjukkan bahwa tidak ada pengaruh signifikan dari penerapan pembelajaran e-learning terhadap hasil belajar mahasiswa.